Recommendations from a James Lind Alliance priority setting partnership - a qualitative interview study - Jongsma, Karin; van Seventer, Juliette; Verwoerd, Anouk; van Rensen, Annemiek (Research involvement and engagement, 2020)
The James Lind Alliance (JLA) offers a method for research priority setting with patients, clinicians and carers. The method is increasingly used but publications primarily discuss the outcome of such projects, rather than reflecting on the JLA method itself. Scrutiny of the method is crucial in order to understand and correctly interpret its outcomes. We conducted a qualitative interview study with people involved in a JLA project into Juvenile Idiopathic Arthritis (JIA) (n = 30) to better understand the mechanisms, procedures and decisional processes during such a project and to formulate recommendations for those who consider starting a JLA project in the future. Four main themes were identified: 1) motivations, goals and expectations 2) inclusivity, roles and representation 3) procedures and decision-making 4) outcomes and future steps. While the top 10 of 'evidence uncertainties' seems to take the centre stage in JLA projects, the ways in which these priorities are determined may be influenced by 'process uncertainties'. We have formulated ten specific recommendations for future JLA projects. Reflection on and reporting of these process uncertainties would contribute to the improvement of JLA projects and increase the validity of the outcome of such projects.